Dosaje de Colinesterasa Serica en trabajadores bananeros expuestos a plaguicidas organofosforados (HCDA. La Italia) del cantón Balao provincia del Guayas - Román Cárdenas, Wilmer G. (2006)
He was carried out the determination of the activity of the seric cholinesterase in 59 biological samples (59 samples of exposed workers to organofosforic pesticides) coming from the treasury Italy of the canton Balao country of Guayas